Soraya the converted a conversation with a Maranao Muslim woman in the Southern Philippines - Hawkins, Michael C. (Silliman Journal, 2007)
This article is a narrative account of a conversion with Maranao Muslim woman in Cagayan de Oro's Cogon Market. It is a part of a larger project I am currently working on. The purpose of this piece is simply to capture a slice of the human experience and to present the subject's voice relatively uninterrupted. Soraya's life experiences touch on a number of important issues including gender and ethno-religious conflict in Mindanao. Her views and attitudes provide interesting and important insights into the Muslim experience in northern Mindanao.